Recent Advances and Challenges in Electrocatalytic Carboxylation of CO2 - Wang, Jie; Wei, Zhen-Feng; Luo, Yun-Xia; Lu, Chang-Hai; Song, Ren-Jie (SynOpen, 2024)
The electrochemical fixation of carbon dioxide onto organic matter has emerged as a promising approach in recent years. By combining the unique features of electrochemistry with the goal of carbon dioxide fixation, researchers aim to develop new strategies that can contribute to a more sustainable and environmentally friendly synthesis of organic compounds. One advantage of electrochemical methods is their ability to provide both electrons and energy for chemical transformations. This allows for the direct conversion of carbon dioxide into valuable organic products, without the need for transition metal catalysts or harsh reaction conditions. As a result, electrochemical carbon dioxide fixation offers the potential for milder and more efficient processes compared to traditional methods. Scientists have made noteworthy progress in exploring different strategies for the fixation of carbon dioxide under electrochemical conditions. These strategies involve the activation of various types of chemical bonds, including C(sp2)–C(sp2), C(sp2)–H, C–X (X = halogen), and C(sp3)–X (X = S, C, O, N). This review aims to provide an overview of the current state of research on electrochemical carbon dioxide fixation into organic matter. It will discuss the different strategies employed, the key findings, and the challenges that remain to be addressed. By highlighting the recent advancements in this field, this review hopes to inspire further exploration and innovation in the area of electrochemical synthesis for carbon dioxide fixation.1 Introduction2 Electrocatalytic Monocarboxylation of CO22.1 Monocarboxylation of C(sp2)–C(sp2)2.2 Monocarboxylation of C(sp2)–H2.3 Monocarboxylation of C–X (X = Cl, Br, I)2.4 Monocarboxylation of C(sp3)–X (X = S, C, O, N)3 Electrocatalytic Dicarboxylation of CO24 Electrocatalytic Esterification of CO25 Conclusions
Keywords: electrochemical; carbon dioxide; carboxylation; esterification; chemical selectivity